Adverse childhood experiences and alcohol related negative consequence among college student drinkers. (January 2023) - Forster, M.; Rogers, C.J.; Tinoco, S.; Benjamin, S.; Lust, K.; Grigsby, T.J.
Highlights: Adverse childhood experiences increase risk for alcohol related negative consequences over and above drinking frequency and risky drinking patterns. The association between adverse childhood experience and alcohol related negative consequence is stable across binge drinking and drinking frequency. There are ethnic differences in the association between adverse childhood experiences and alcohol related negative consequences that need further investigation. Abstract: Objective: Despite increasing college campus prevention efforts, and identification of effective strategies to reduce drinking, reducing alcohol related negative consequences (ARNC, e.g., regrets, blackouts, self- and other- injury, law enforcement exposure, sexual assault, and considering suicide) continues to be a challenge. While college students with a history of adverse childhood experiences (ACE) are at greater risk for alcohol misuse, research regarding the association between ACE and ARNC remains limited. Methods: Data are responses of currently drinking students on the American College Health Association-National College Health Assessment (ACHA-NCHA II) and College Student Health Survey (CSHS), administered in 2018 to students in California and Minnesota (N = 6, 667). Results: On average, students reported one ARNC (SD = 1.30) although 13 % experienced three or more different types of ARNC in the past year. Every ACE was associated with a 19 % to 41 % increase in the IRR of ARNC. Students with 1–3 ACE experienced significantly more types of ARNC events (IRR 1.55, 95 % CI: 1.44–1.67) than students with no ACE and students with ≥ 4 ACE experienced statistically significantly more types of ARNC events (IRR 2.04, 95 % CI: 1.82–2.31) than their peers with 1–3 or no ACE. The ACE-ARNC relationship did not vary by drinking frequency or binge drinking. Conclusions: The consistent ACE - ARNC relationship across drinking behaviors suggests alcohol consumption does not fully explain the association between ACE and ARNC and that early adversity heightens vulnerability for ARNC. Implications for future prevention and intervention efforts are discussed.